\(x^4+6x^3+7x^2-6x+1\)
\(=x^4+6x^3+9x^2-2x^2-6x+1\)
\(=\left(x^2\right)^2+2.x^2.3x+\left(3x\right)^2-2\left(x^2+3x\right)+1\)
\(=\left(x^2+3x\right)^2-2\left(x^2+3x\right).1+1^2\)
\(=\left(x^2+3x-1\right)^2\)
Chúc bạn học tốt.
\(x^4+6x^3+7x^2-6x+1\)
\(=x^4+6x^3+9x^2-2x^2-6x+1\)
\(=x^2\left(x+3\right)^2-2\left(x^2+3x\right)+1\)
\(=\left(x^2+3x\right)^2-2\left(x^2+3x\right)+1=\left(x^2+3x-1\right)^2\)
https://olm.vn/hoi-dap/tim-kiem?q=Cho+%CE%94ABC+vu%C3%B4ng+t%E1%BA%A1i+A+c%C3%B3+AB+%3E+AC,+M+l%C3%A0+%C4%91i%E1%BB%83m+tu%E1%BB%B3+%C3%BD+tr%C3%AAn+BC.+Qua+M+k%E1%BA%BB+Mx+vu%C3%B4ng+g%C3%B3c+v%E1%BB%9Bi+BC+v%C3%A0+c%E1%BA%AFt+AB+t%E1%BA%A1i+I+c%E1%BA%AFt+CA+t%E1%BA%A1i+D.a.+Ch%E1%BB%A9ng+minh+%CE%94ABC+%C4%91%E1%BB%93ng+d%E1%BA%A1ng+v%E1%BB%9Bi+%CE%94MDCb.+Ch%E1%BB%A9ng+minh:+BI.BA+=+BM.BCc.+Cho+g%C3%B3c+ACB+=+60o+v%C3%A0+S%CE%94CDB+=+60+cm2.+T%C3%ADnh+S%CE%94CMAGi%C3%BAp+m%C3%ACnh+c%C3%A2u+c+v%E1%BB%9Bi&id=573451